Magnetism of N-doped graphene nanoribbons with zigzag edges from bottom-up fabrication. Issue 12 (25th January 2016) - Xu, Jie; Zhang, Weifeng; Wei, Congyuan; Huang, Jianyao; Mao, Zupan; Yu, Gui
Abstract : Two graphene nanoribbons with atomically precise N-doping zigzag edges from bottom-up fabrication by a condensation reaction exhibited intrinsically magnetic properties with a maximum magnetization of 0.303 emu g −1 . Abstract : Graphene nanoribbon is a promising architecture for the development of advanced spintronic and other electronic-based devices. However, experimentally researching the magnetic properties of graphene nanoribbons is often obstructed by the key challenges in the synthesis of how to obtain the required chemical precision for control over edge structures and width. Here we synthesized two graphene nanoribbons with atomically precise N-doping at zigzag sites prepared from bottom-up fabrication by a condensation reaction. Our work clarifies the experimental issue of graphene nanoribbon's magnetism. Two graphene nanoribbons lead to notable paramagnetism, which is not from residual magnetic impurities. In the process of optimizing the preparation conditions, we found that the elevated synthesis pressure and using 1-methyl-2-pyrrolidinone as solvent could lead to production of larger graphene nanoribbon skeletons with N-doped zigzag edges and then to improve the magnetization. These results provide a feasible and very attractive strategy to achieve the required atomic precision and experimentally guide future research for the magnetic properties of graphene-based materials by changing reaction precursors.